Training and Assistance in Financial Administration Report Preparation Using Microsoft Excel - Andi Jaman; Agusdiwana Suarni; Muhammad Khaedar Sahib (Universitas Muhammadiyah Sidoarjo, 2023)
This article presents the outcomes of the Program Pengabdian Kepada Masyarakat (PKM) undertaken by a social movement organization in Indonesia. The program aimed to enhance the financial reporting capabilities of its leadership through a three-phase approach comprising training, mentoring, and evaluation of financial administration records. Virtual pre-training equipped participants with essential Excel and financial application skills. The results showed a significant improvement in financial reporting, ensuring transparency and accountability. Moreover, the financial administration training facilitated better planning and informed decision-making, fostering sustainable development. These implications resonate globally, encouraging similar community engagement initiatives to advance financial transparency and effectiveness. Highlights: Enhanced Financial Reporting: The three-phase approach led to a significant improvement in the organization's financial reporting capabilities, ensuring greater transparency and accountability. Empowered Decision-Making: The financial administration training enabled better planning and informed decision-making, contributing to the sustainable development of the social movement organization. Global Implications: The program's success inspires related scientists and organizations worldwide to implement similar community engagement initiatives, advancing financial transparency and effectiveness on a broader scale. Keywords: Financial reporting, Community engagement, Sustainable development, Training, Transparency